2010
DOI: 10.1111/j.1440-1746.2009.06109.x
|View full text |Cite|
|
Sign up to set email alerts
|

Successful stenting in ductal disruption favorably impacts treatment outcomes in patients undergoing transmural drainage of peripancreatic fluid collections

Abstract: Transpapillary PD stenting improves treatment outcomes in patients undergoing endoscopic transmural drainage of PFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 23 publications
2
75
0
Order By: Relevance
“…In 563 patients with pseudocysts, they found that spontaneous resolution occurred only in 0%5% of patients with a ductal disruption compared to 87% of patients with a normal pancreatic duct. Similarly, Trevino et al [108] demonstrated improved PFC resolution of both pseudocysts and WOPN in patients who underwent PFC drainage with transpapillary PD stenting compared with PFC drainage alone (97.5% vs 80%). Of note, undergoing ERCP was not associated with any increase in mortality, the need for necrosectomy, or hospital length of stay.…”
Section: Pd Disruption and Pfc Resolutionmentioning
confidence: 84%
“…In 563 patients with pseudocysts, they found that spontaneous resolution occurred only in 0%5% of patients with a ductal disruption compared to 87% of patients with a normal pancreatic duct. Similarly, Trevino et al [108] demonstrated improved PFC resolution of both pseudocysts and WOPN in patients who underwent PFC drainage with transpapillary PD stenting compared with PFC drainage alone (97.5% vs 80%). Of note, undergoing ERCP was not associated with any increase in mortality, the need for necrosectomy, or hospital length of stay.…”
Section: Pd Disruption and Pfc Resolutionmentioning
confidence: 84%
“…19,20 As mentioned above, the use of transpapillary stenting appeared to provide no additional benefit in patients that already received transmural drainage. However, in two studies, it was suggested that if the pancreatic duct stent could bridge the site of leak, treatment success rate was higher.…”
Section: Adjunctive Measures To Pseudocyst Drainagementioning
confidence: 95%
“…Complications occurred in 11% of cases, after a mean follow-up of 22 months [29]. In patients with a pancreatic duct disruption that could be bridged, transpapillary pancreatic duct stenting improved outcomes in patients with endoscopic transmural drainage of peripancreatic fluid collections [30]. Trevino et al reviewed 110 patients with endoscopic transmural pancreatic fluid collection drainage (62% pseudocysts), in 40 (36%) patients being added a simultaneous pancreatic duct stenting [30].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a pancreatic duct disruption that could be bridged, transpapillary pancreatic duct stenting improved outcomes in patients with endoscopic transmural drainage of peripancreatic fluid collections [30]. Trevino et al reviewed 110 patients with endoscopic transmural pancreatic fluid collection drainage (62% pseudocysts), in 40 (36%) patients being added a simultaneous pancreatic duct stenting [30]. Even after multivariable analysis, the patients with a pancreatic duct stenting were significantly more likely to have a treatment success (risk ratio 1.14, 95% confidence interval: 1.01-1.29, p=0.0036).…”
Section: Discussionmentioning
confidence: 99%